Implementasi Peran Kepemimpinan dalam Kolaborasi Multiprofesi di Rumah Sakit Pendidikan : Literature Review - Eka Safitri; Rinawati Rinawati (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
Implementation of leadership in multiprofessional roles within teaching hospitals. The analysis focuses on leadership styles (transformational, green, situational, sustainable), interprofessional educational interventions, and their effects on collaboration, innovation, and staff wellbeing. Key findings indicate that transformational and green leadership enhance collaboration, environmental innovation, and staff wellbeing; situational approaches raise team situational awareness; and interprofessional training builds readiness and positive interprofessional perceptions. These results support the development of structured cross-professional leadership programs in teaching hospitals to foster effective collaboration, quality care, and clinical education synergy.